Innovative development on a p-type delafossite CuCrO₂ nanoparticles based triethylamine sensor - Liu, Hai (2022)
Metal oxide semiconductors are recognized as an excellent underlying substance for the assembly of gas sensors to detect the volatile organic compounds in industry or healthcare, but are constrained by their low selectivity and high operation temperature. In the present paper, we present a nanostructured p-type delafossite CuCrO2, synthesized by the hydrothermal method, that provides a high selectivity, stability and high dynamic response to triethylamine at a low temperature of 140 ℃. In-situ heating spectrum analysis and systematic gas sensing tests with the assistance of first principles calculations based on the density functional theory demonstrate that this ternary oxide takes a unique synergy mechanism for gas sensing process, rather than the ionosorption effect of ambient oxygen. It starts with the adsorption of gas molecules to the unsaturated coordinative metal sites of Cr, which is then followed by the dehydrogenation on Cu resulting in the formation of oxygen vacancies. This gas sensing mechanism successfully explains the extraordinary properties of CuCrO2 nanoparticles as a triethylamine sensor. This work delivers an exploratory approach to the assigned interaction of gas molecules and the sensitive layer at atomic scale, which provides ways to design and develop more advanced gas sensors for other material systems.